Wetting of monocrystalline silicon (100) surface by Sn0.3Ag0.7Cu-xTi (x = 1 and 3 wt%) alloys at 800–900 °C. (January 2020) - Wang, Jianbin; Lin, Qiaoli; Li, Hui; Mu, Dekui
Abstract: The wetting of monocrystalline Si by molten Sn0.3Ag0.7Cu(SAC)- x Ti ( x = 1, 3 wt%) was studied by using the modified sessile drop method at 800–900 °C under a high vacuum. The results showed that the added Ti in SAC- x Ti/Si system can improve wettability slightly, from 63 o without Ti addition at 800 °C to 42 o with 1 wt% Ti addition at 900 °C. The system (Ti ≤ 3 wt%) has an inert interface without the precipitation of reaction product, and the addition of active component Ti enhanced the dissolution of monocrystalline Si substrates into liquid but not participated in interfacial reaction. In the process of melt spreading, the pyramidal morphology appeared at the interface by the re-deposition mechanism and micro-mask mechanism, which cannot improve the wettability of the system but worsen wettability conversely by the pinning of triple line. Highlights: Ti additions enhanced dissolution of Si into liquid. Pyramidal morphology was formed by anisotropic etching and re-deposition. Ti additions only can slightly improve wettability in SAC- x Ti/Si system.